Review Essay: Perspective and Balance: Considering Qualitative Research Methods in Psychology - Magee, Vicki L. (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2002)
Mary KOPALA and Lisa A. SUZUKI's edited volume, Using qualitative methods in psychology, offers a great deal in its 237 pages and is a must read for anyone interested in more fully understanding the conversation on this topic. The authors of the book's seventeen chapters address such questions as: why has psychology placed primacy on quantitative methods; how reliable are the results of qualitative research; how can quantitative and qualitative approaches be combined; what ethics guide this approach; and what is needed to get qualitative articles published in reputable journals? Nearly half of the chapters provide excellent examples of qualitative research investigations in psychology. Although the book has some limitations, KOPALA and SUZUKI's book fills a gap in psychological literature regarding the use of qualitative research methods in psychology.URN: urn:nbn:de:0114-fqs0201234